Interacting with latter-day musical automata. - Lewis, George E. (Contemporary Music Review, 1999)
The idea of music that somehow plays itself, or emerges from a nonhuman intelligence, is a common, transculturally present theme in folklore, science, and art. Over the centuries, this notion has been expressed through the development of various technological means. This paper explores aspects of my ongoing encounter with computers in improvised music, as exemplified by my most recent interactive computer music compositions. These works involve extensive interaction between improvising musicians and computer music-creating programs at the performance ("real-time") level. In both theory and practice, this means that both human musicians and computer programs play central organizing and structuring roles in any performance of these works. This paper seeks to explore aesthetic, philosophical, cultural and social implications of this work. In addition, the nature and practice of improvisation itself will be explored, since an understanding of this ubiquitous musical activity is essential to establishing the cultural and historical context of the work.